Influence of landscape structure on the abundance of Desmodus rotundus (Geoffroy 1810) in northeastern Yucatan, Mexico - Bolívar-Cimé, Beatriz; Flores-Peredo, Rafael; García-Ortíz, Scarlett Aislinn; Murrieta-Galindo, Rene; Laborde, Javier (Ecosistemas y Recursos Agropecuarios, 2019)
Although the transformation of landscapes by human activity can negatively affect the populations of several bat species, other species may benefit from these transformations. One of such species is the vampire bat, Desmodus rotundus, which can often be found in landscapes dominated by livestock activities. Furthermore, there are certain structural landscape characteristics that could be positively influencing the abundance of the vampire bat. To assess this possibility, eight sampling sites in northeastern Yucatan, Mexico were monitored from June 2010 to February 2012. Four sites were located in forest fragments amongst a highly fragmented landscape dominated by pastures dedicated to livestock activities, and four sites were located within continuous tropical semideciduous forest with almost no fragmentation. Forest fragmentation was characterized around the sampling sites within a 2.5 km radius using SPOT images from 2010, and five landscape variables were calculated using FRAGSTATS. The results showed that landscape heterogeneity and an agricultural aggregation index both had a significant effect on the abundance of the vampire bat. Our results showed that D. rotundusabundance in northeastern Yucatan, Mexico was favored by extensive pastures as well as by landscape characteristics associated with intense forest fragmentation. However, the presence of some remnants of forest cover probably enhance the movements and persistence of this species. To reduce the negative impact of the vampire bat presence in these areas dedicated to livestock ranching activities, effective preventive vaccination campaigns could be an important strategy.